Praktični pristop k obravnavi glavkoma - Cvenkel, Barbara (Zdravniški vestnik, 2010)
Algorithms for management of glaucoma suspects and glaucoma patients are presented. After obtaining medical and ocular history, clinical examination and visual field testing a working diagnosis is established. Staging is assigned to glaucoma suspect according to the risk factors present and to glaucoma patients according to the severity of disease. The treatment is guided by the severity of disease, patientćs life expectancy, the state of thefellow eye, risk factors and presence of other systemic diseases. At follow-up clinical examination and visual field testing are performed to determine the rate of progression. The main reasons for referral to Glaucoma unit are elucidated and discussed.
Keywords: Diagnosis; Glaucoma; Glavkom; Ocular Hypertension; oftalmologija; Oko, hipertenzija; Practice Guidelines; Praktična navodila; Scotoma; Skotom; smernice; Therapy; Tonometrija; Tonometry; Vidna polja; Visual Fields; zdravljenje